Life cycle analysis of a hybrid direct air capture system enabling combined carbon dioxide and water extraction from ambient air - Stephen McCord; Ana Villa Zaragoza; Volker Sick; Yanhui Yuan; Alexander Spiteri; Benjamin A. McCool; Ronald R. Chance (Carbon Capture Science & Technology)
This study details a life cycle analysis (LCA) of a hybrid direct air capture (HDAC) system which integrates moisture swing adsorption (MSA) and atmospheric water extraction (AWE) technologies for the simultaneous capture of CO2 and water from ambient air. A HDAC plant with an annual capture capacity of 3000 tonne CO2 per year is modeled and life cycle impacts assessed for two locations (California and Louisiana) considered as potential deployment sites. The system is powered solely by electricity and is heat integrated across major sources and sinks in order to increase efficiency. A range of deployment scenarios are considered, varying both electricity source and the operational performance of the plant. Five electricity sources are considered based on the maturity of the electricity production processes and the practicality of their use at the chosen sites. The aim of this study is the evaluation of the viability of these potential deployment scenarios based on assessed life cycle impacts. In the majority of the deployment cases, electricity production dominates the global warming impacts related to capture, compression and sequestration of CO2. The impacts related to non-electricity contributions are also explored, where it is found that the construction materials of the plant can have a notable impact in sufficiently decarbonized electricity scenarios. Sorbents are shown to have a minimal impact (carbon burden about 1 %) in agreement with previous studies. Significant net removals of CO2 from the atmosphere are found for all scenarios considered with the carbon burden for full plant operation (capture to sequestration) ranging from 3.5 % to 64.0 % dependent mainly on the carbon intensity of the power source. A broader environmental impact assessment suggests no immediate concerns when selecting between nuclear, wind or solar power for plant operation.